Steroidal Hormone Receptor Expression in Male Breast Cancer - Fatemeh Homaei-Shandiz; Abdolazim Sedighi; Noorieh Sharifi Sistani (Mashhad University of Medical Sciences, 2014)
Introduction: The etiology of male breast cancer is unclear, but hormonal levels may play a role in development of this disease. It seems that the risk of male breast cancer related to increased lifelong exposure to estrogen or reduced androgen. The aim of this study was to investigate the expression of the steroid hormone receptors including estrogen receptor (ER) and progesterone receptor (PR) in Iranian cases with male breast cancer. Methods: This is a prospective review of 18 cases of male breast cancer in in Omid Hospital, Mashhad, North East of Iran, between October 2001 and October 2006. ER and PR were measured by immunohistochemistry. Clinicopathologic features and family history were obtained by interview. Data were analyzed with SPSS 13 using descriptive statistics.  Results: The median age was 63.2 year. All the cases were infiltrating ductal carcinoma. A high rate of expression of ER (88.8%) and PR (66.6%) was found in the studied cases. Conclusion: Cancers of the male breast are significantly more likely than cancers of the female breast to express hormonal receptors.